FORMATION AND ACTIVITIES OF POLITICAL PARTIES OF THE RUSSIAN FEDERATION IN THE 1990s (REGIONAL CONTEXT) - N. Shaozheva; M. Gugova (Гуманитарные и юридические исследования)
The article analyzes the formation of political parties in the 1990s in Russia. It is shown that after the CPSU left the political arena on its basis, various parties adhered to traditionalist (communist) ideology were created, and on the basis of the Democratic Party of Russia formed political organizations and movements mainly liberal. Centrists in the party system were the «third power» - the «party of power.» Against this background, in the 1990s, the regional branches of all-Russian political parties and movements were formed in Kabardino-Balkariya, which played a role in the political space of the region. The relevance of the stated theme is due to the fact that the transformation of the communist regime, accompanied by political and socio-economic transformations, has formed the specifics of the liberalization of Russian society. It was that it was the ruling communist and post-communist political elite that initiated reforms, played a key role in party building and tried to maintain control over political processes, including in Kabardino-Balcaria. The main sources of the study were archival materials collected at the Centre for Documentation of the Recent History of the Kabardino-Balkar Republic, which contain detailed data to examine the issues related to the formation and activities of regional ofices of federal political parties during the historical period. Information from archival statistics is supplemented by published information from the media. It is concluded that the party-management in Kabardino-Balkariya in the 1990s began later than at the federal level and was the result of general trends of Russian party building. It is significant that in the region with the advent of liberal-democratic parties, a certain party competition has begun. Lacking signiicant political resources and party building mechanisms, the regional branches of the federal parties of the CBD were formed as electoral headquarters during the period of elected companies and participated mainly in all-Russian events.